Глобальные слабые решения системы Навье - Стокса - Фоккера - Планка - Егоров, С.М.; Хруслов, Е.Я. (Український математичний журнал, 2013)
Розглядається зв’язана система рiвнянь Нав’є – Стокса i Фоккера – Планка, що описує рух полiдисперсної суспензiї твердих часток у в’язкiй нестискуванiй рiдинi. Доведено iснування i вивчено деякi властивостi глобальних слабких розв’язкiв початково-крайової задачi для цiєї системи. We consider a coupled system of the Navier–Stokes and Fokker–Planck equations used to describe the motion of a polydispersed suspension of solid particles in a viscous incompressible fluid. We prove the theorem on existence of solutions and study some properties of global weak solutions of the initial boundary-value problem for this system.